Comparison of pachymetry values during crosslinking with different riboflavin solutions (Annals of Medical Research, 2023)
Aim: To compare the effect of two different riboflavin solutions we use in the accelerated crosslinking (CXL) process on the pachymetry value.Materials and Methods: Patients who had accelerated CXL treatment with dextran-free riboflavin solution due to progressive keratoconus were retrospectively screened. Thirty-seven eyes of 27 patients (group 1) treated with Hydroxyl Propyl MethylCellulose (HPMC) and 0.1% riboflavin containing solution and 29 eyes of 23 patients (group 2) treated with D-alpha-tocopheryl polyethylene-glycol 1000 succinate (VE-TPGS) and 0.1% riboflavin containing solution were compared in terms of pachymetry changes during treatment.Results:  In groups 1 and 2, the mean age was 23.92 ± 5.66 and 23.30 ± 4.89, respectively. Mean age, gender, initial keratometry values, mean central corneal thickness (CCT) before (p = 0.158) and after epithelial debridement (p= 0.320) did not differ significantly between the two groups (p>0.05). The CCT measured after riboflavin instillation was 453.22 ± 37.48 μm in the group 1 and 479.34 ± 38.54 μm in the group 2 (p=0.007). After instillation of riboflavin, according to the initial CCT, there was an average thinning of 21.57 ± 16 μm in the group 1 and 18.72 ± 22.13 μm thickening in the group 2 (p
Keywords: Crosslinking; Pachymetry; Riboflavin